Perancangan Interior M&Mâs Choco Candy World di Surabaya - Grace Mulyono, Angeline Ariesta (Intra, 2014)
Candy and chocolate are well- known snack by pople. Because its taste and sweetnes, candy and chocolate is often used as a snack in between meals. Visualization of shape, color, and attractive packaging also be an attraction of sweets and chocolate to be consumed. One brand that is quite popular chocolate candy is M&Ms. M&Ms also have different types of milk sweets and also the preferred brand character. M & Ms outlets are spread throughout the country like London, U.S, Las Vegas, and many other countries. However Outlet M&Ms are still not in Indonesia today. Therefore, the design of the M&Ms outlet is required to provide satisfaction for candy and chocolate lovers, and can also provide an alternative for family entertainment venues in addition to the mall.Â